APLIKASI EKSPLORASI VIRTUAL MUSEUM NEGERI PROVINSI SULAWESI UTARA - Oktoverano Lengkong; Andria Wahyudi; Reynald G K Lumantouw (CCIT Journal, 2018)
Information is important in adding insight and knowledge, if the information can be processed properly and can be delivered properly, then this information can be used as needed. By using technology support, information becomes easier to process and deliver. Virtual Tour, is a technology created to provide information in digital form.Virtual tour has been widely used to introduce a virtual building, but for museum building is rarely available even in North Sulawesi yet. North Sulawesi is part of eastern Indonesia with Manado as the capital has a museum that is the State Museum of North Sulawesi Province. Then the application is developed for the exploration of the State Museum of North Sulawesi province with features of first person view using Unity 3D as a game engine and Google SketchUp as a 3D modeler. The development of this application uses the spiral model and the research methods used are observation and study literature. This application was created to attract visitors to come to the museum and hopefully this application can help visitors to find out more information of historic objects in the museum's main building.